Pengaruh Berbagai Takaran Pupuk Organik Cair Limbah Tahu dan Urea terhadap Nodulasi, Serapan N, dan Pertumbuhan Tanaman Kacang Tanah (Arachis hypogaea L.) - Putu Putriyani Megantari; Ni Wayan Dwiani Dulur; I Putu Silawibawa (Journal of Soil Quality and Management, 2022)
The purpose of this study was to determine the effect of giving various doses of liquid organic fertilizer of tofu (POC) and urea on nodulation, N uptake and growth of Peanut plants (Arachis hypogaea L.) in the maximum vegetative phase of the plant. The research method used an experimental method with seven treatments. Each treatment had 3 replications so it consisted of 21 experimental units. The research was conducted April-August 2020 in Dasan Tebu Village, Ombe Baru Village, Kediri District, West Lombok Regency. The treatments used were P0 (without treatment), P1 (50 kg Urea / ha + 10,000 l POC / ha), P2 (50 kg Urea / ha + 15,000 l POC / ha), P3 (50 kg Urea / ha + 20,000 l POC / ha), P4 (100 kg Urea / ha + 10,000 l POC / ha), P5 (100 kg Urea / ha + 15,000 l POC / ha), P6 (100 kg Urea / ha + 20,000 l POC / ha). The parameters tested in this research is the growth of peanut, the total amount root nodules, the wet stover weight of root nodules, the N content of tissue, the plant's wet stover, the plant's dry stover, the N uptake of plants, soil pH and N-available soil. The treatment did not affect the number of nodules, N uptake, plant height, plant wet stover weight and available N-NO3-. However, it has an effect on root nodule wet stover weight, nitrogen on tissue plant, plant dry stover, soil pH, and available N-NH4+.